Plan de marketing relacional para la fidelización de clientes empresa Industrias Alimenticias Carolina S.A.S. (INDACAROL – Villavicencio) Proyecto de Grado (2021)
Currently, relationship marketing plays a fundamental role in companies, through customer loyalty, attracting more prospects which generates greater profitability for the organization, so it was decided to propose a relationship marketing plan to the INDACAROL company SAS in order to generate new strategies that allow better development in commercial and sales processes. Therefore, in this project different evaluative tools were applied, such as surveys of clients, collaborators and suppliers in order to establish a situational diagnosis through the SWOT matrix, thus measuring its impact with the help of an internal and external analysis to through the application of the PCI and POAM matrix. The objective of this project was to design a marketing plan taking advantage of all the tools mentioned above, thus making an optimal diagnosis that would allow the development of marketing strategies that can be applied and measured in the company INDACAROL S.A.S. in order to achieve long-term customer loyalty.